Estimation of Suaeda aegyptiaca Plant distribution regions at Iraq using RS & GIS Applications - Al Ramahi, Fouad K. Mashee; Al Bahadly , Zina Khalil Ibrahim (Iraqi Journal of Science, 2022)
For ecosystem functions factors monitored the natural changing of environmental systems, and the managing ability expectation or prediction the plantation regions, (e.g. desert decreasing, air pollution reducing and weather wet stabilization). How, depends on the ability to understand how a particular ecosystem functions and the automation that control the elements distribution, such as (Suaeda aegyptiaca) plant in this study. Which recognized plants Iraq native, and, that are widely found in some regions of Iraq finding randomly. Amplitude plantations regions and automation wealth can be observed diffusion and growth this plantation, as well as estimated the far-reaching and unknown locations to form control and improve environmental and ecosystem relief.We will be used Botany mapping techniques, this map is identified many indicators about the spatial variability distribution areas, and the maps can be a clear indication display significant spatial points of environmental. This process Required different techniques such as spatial description locations.For purpose, this study applied RS, GIS techniques and Kernel density estimation (KDE) achievement this study.